GENDER DIFFERENCES AND LANGUAGE LEARNING STRATEGIES OF INDONESIAN STUDENTS: A CRITICAL RESEARCH REVIEW - Martina, Martina; Afifi, Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study explores gender differences in language learning strategies (LLS) within the Indonesian context. Drawing on various studies, it reveals mixed results regarding the preference for strategies between male and female students. Some studies, such as Budiarti (2022), report no significant gender differences, while others (e.g., Rianto, 2020; Melvina et al., 2020) suggest that female students, particularly those with higher English proficiency, use strategies more frequently. Female learners tend to prefer metacognitive strategies (e.g., planning and self-monitoring), while male students lean toward cognitive strategies (e.g., memorization) and social strategies (e.g., peer interaction). The study highlights strengths in the use of validated instruments like the Strategy Inventory for Language Learning (SILL) but also identifies weaknesses such as response bias and limited consideration of contextual factors like motivation and social support. These findings indicate that gender influences strategy use, but external factors, including proficiency and motivation, also play significant roles. The research recommends adopting more comprehensive research methods and practical teaching approaches that account for gender-specific strategy preferences, thus fostering more inclusive language learning environments. This study contributes to both theoretical and practical insights in foreign language education in Indonesia.